Operando NRIXS and XAFS Investigation of Segregation Phenomena in Fe‐Cu and Fe‐Ag Nanoparticle Catalysts during CO2 Electroreduction. Issue 50 (6th October 2020) - Kunze, Sebastian; Grosse, Philipp; Bernal Lopez, Miguel; Sinev, Ilya; Zegkinoglou, Ioannis; Mistry, Hemma; Timoshenko, Janis; Hu, Michael Y.; Zhao, Jiyong; Alp, Ercan E.; Chee, See Wee; Roldan Cuenya, Beatriz
Abstract: Operando nuclear resonant inelastic X‐ray scattering (NRIXS) and X‐ray absorption fine‐structure spectroscopy (XAFS) measurements were used to gain insight into the structure and surface composition of FeCu and FeAg nanoparticles (NPs) during the electrochemical CO2 reduction (CO2 RR) and to extract correlations with their catalytic activity and selectivity. The formation of a core–shell structure during CO2 RR for FeAg NPs was inferred from the analysis of the operando NRIXS data (phonon density of states, PDOS) and XAFS measurements. Electrochemical analysis of the FeAg NPs revealed a faradaic selectivity of 36 % for CO in 0.1 M KHCO3 at −1.1 V vs. RHE, similar to that of pure Ag NPs. In contrast, a predominant selectivity towards H2 evolution is obtained in the case of the FeCu NPs, analogous to the results obtained for pure Fe NPs, although small Cu NPs have also been shown to favor H2 production. Abstract : Operando nuclear resonant inelastic X‐ray scattering (NRIXS) and X‐ray absorption fine‐structure spectroscopy (XAFS) measurements were used to gain insight into the structure and surface composition of FeCu and FeAg nanoparticles (NPs) during the electrochemical CO2 reduction (CO2 RR) and to extract correlations with their catalytic activity and selectivity.